An Ottoman map of Sanjak of Herzegovina and Sanjak of Scutari from 1853 - Elma Korić (Bosniaca)
The goal: The aim of the work is to draw attention to the cartographic material of Ottoman origin as a very exhaustive historical source for the study of the history of Bosnia and Herzegovina. Approach/methodology/design: In the course of the research, an insight was made into the historiographical production so far in order to determine to what extent cartographic material of Ottoman origin was recognized as a historical source. A comparative analysis of the content offered by the found map from 1853 compared to earlier Ottoman maps showing the territory of today’s Bosnia and Herzegovina and its surroundings was performed. The paper presents the basic characteristics and content of the mentioned map and tried to figure out the reasons and context of its creation. The results: In principle, the found cartographic material provides prerequisites for a more detailed approach to the study of the general history of Bosnia and Herzegovina based on the mentioned sources. The map analyzed here provides new data on the administrative arrangement of the Bosnian eyalet in the middle of the 19th century, the borders of the mentioned area, the location of deposits of mineral resources, and the like. Restrictions: Since only one map from the entire corpus of maps of Ottoman origin found so far, on which the territory of today’s Bosnia and Herzegovina is represented, was analyzed, the final results of the research will be presented only after processing the entire corpus. Practical application: The practical application of this research is reflected in the fact that the new data offered by the map will be able to be incorporated into the scientific material not only of specialized literature but also of school textbooks. In addition, information on potential deposits of various ores can represent a guideline in the specified branch of industry. Originality/value: The presentation of cartographic material of Ottoman origin of this area is a novelty because the content of the mentioned maps as well as the notes it offers are written in Arabic script in the Ottoman Turkish language, which makes it a complex material for research. With this work, he provides the scientific, professional and general public with some of the useful material contained in the maps.